Palaeogeography and geomorphological evolution of Akrotiri Salt Lake, Lemesos, Cyprus - Polidorou, M.; Evelpidou, N.; DRINIA, H.; Tsourou, T.; Salomon, F.; Blue, L. (RCG2019 “Geomorphology of Climatically and Tectonically Sensitive Areas”, 2019)
Akrotiri Salt Lake is located 5km west of the city of Lemesos, in the southern-most part of the island of Cyprus. The palaeogeographic evolution of the Akrotiri Salt Lake presents a great scientific interest, especially during the Holocene where the eustatic movements combined with local active tectonics and climate changes have developed a unique geomorphological environment. The Salt Lake, today a closed lagoon, which is depicted in Venetian maps (Bordon AD 1528) as being connected to the sea, can provide evidence of the geological settings and landscape evolution of the area. In this study, we investigate the development of Akrotiri Salt Lake through a series of cores which penetrated the Holocene sediment sequence. Sedimentological, micropaleontological (benthic foraminifera and ostracods) analyses and geochronological studies performed on deposited sediments, identifying the complexity of the evolution of the Salt Lake and the progressive change of the area from maritime space to an open bay and finally to a closed Salt Lake.